Kosovo--macroeconomic issues and fiscal sustainability - Corker, Robert; Rehm, Dawn Elizabeth, 1953-; Kostial, Kristina ([Washington, D.C.] : International Monetary Fund, 2001)
It is about Kosovo a province of Serbia in the Federal Republic of Yugoslavia that is under temporary UN administration. It indicated the technical assistance granted by IMF staff. The assistance was channeled towards setting up taxation and budgetary instittutions, a payments and banking systems and a more recently , a statistical framework.
Includes bibliographical references.
OPC13/03/15
Loans
Keywords: Budget -- Yugoslavia -- Kosovo (Serbia); Kosovo (Serbia) -- Economic conditions